Effect of Planting Media Composition and Number of Segments on Patchouli Cuttings Growth - Fitri Yetty Zairani; Burlian Hasani (Universitas Muhammadiyah Palembang, 2021)
This study aims to analyze planting media composition and the number of segments of the setek on the growth of patchouli. This study used the Group Randomized Design (RAK) method factorially with nine treatments and three replays. One treatment with 5 sample plants. Treatment consists of a) Composition of plant media (M) namely M0 (topsoil); M1 (topsoil+manure with a ratio of 1:1); M2 (topsoil+ fertilizer drum with a ratio of 1:1), b) Factor number of segments setek (P), namely P1 (3 segments); P2 (4 Segments); and P3 (5 Segments). The results showed the overall percentage of living seedlings is 100%. The treatment of soil planting media mixed with chicken manure (M2) gives good results only to the growth of patchouli roots. The treatment of five segments of setek (P3) has a good influence on the length of the patchouli root. The interaction between soil media mixed with chicken manure fertilizer (M2) with five segments of setek (P3) gives the best influence on the growth of patchouli root length.